The family in India : structure and practice - Patel, Tulsi (Sage Publications, 2005)
This timely book examines, in detail, the meaning of family in India. Inextricably linked to the institution of family are issues such as gender and sexual divisions, the role of the state, changing demographic patterns and a growing elderly population. The first part of the book looks at the nature of the family as an institution. Part Two discusses the question of the myth or reality of the disintegration of the joint family. Finally, the last section includes case studies of structures of families in different parts of India.